2017
DOI: 10.1016/j.diabres.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Second line initiation of insulin compared with DPP-4 inhibitors after metformin monotherapy is associated with increased risk of all-cause mortality, cardiovascular events, and severe hypoglycemia

Abstract: Initiation of insulin, compared with DPP-4i treatment, was associated with an increased risk of subsequent all-cause mortality, fatal and nonfatal CVD, and severe hypoglycemia. Results from randomized trials will be important to elucidate causal relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 34 publications
(49 reference statements)
2
39
1
3
Order By: Relevance
“…To the best of our knowledge, no randomized study using CVD endpoints has compared patients treated with insulin with either DPP‐4 inhibitor and/or SGLT2 inhibitor treatment. In the absence of outcome results from randomized clinical trials, observational studies comparing insulin with alternative per oral GLDs are the best available evidence …”
Section: Discussioncontrasting
confidence: 73%
“…To the best of our knowledge, no randomized study using CVD endpoints has compared patients treated with insulin with either DPP‐4 inhibitor and/or SGLT2 inhibitor treatment. In the absence of outcome results from randomized clinical trials, observational studies comparing insulin with alternative per oral GLDs are the best available evidence …”
Section: Discussioncontrasting
confidence: 73%
“…In general, the use of sulphonylureas is decreasing, however, at a slower pace in Sweden compared to the other three countries. It is clear from that paper that, until recently, Swedish guidelines advocated NPH (neutral protamine Hagedorn, isophane) insulin and SU as second-line therapy, also shown in other observational studies 13. Surprisingly, we found very large differences in second-line treatment initiation between countries, despite similar demography, healthcare education levels and nationwide public healthcare systems.…”
supporting
confidence: 55%
“…13,28 The higher use of statin in Denmark despite the least prevalent CVD population might also reflect the differences in organization and attitudes on CV prevention in T2D across countries. Overall, the regional use of older GLDs displayed opposite differences to the above as ex- commonly have trained staff available to handle initiation of insulin therapy.…”
Section: Regional Differences In Second-line Treatment Within Swedenmentioning
confidence: 99%
“…Patient characteristics included age at the date of index drug, sex, index date, date of first dispensing of a registered GLD, and a description of patient frailty (defined as at least 1 hospitalization of ≥3 consecutive days during the year prior to index date) S1B.…”
Section: Methodsmentioning
confidence: 99%
“…The sodium glucose‐co‐transporter‐2 (SGLT‐2) inhibitors empagliflozin and canagliflozin have recently been shown to be associated with a reduced risk of CV disease and hospitalization for heart failure (HHF) and, in the case of empagliflozin, also a reduced risk of all‐cause mortality, compared with placebo added to existing glucose‐lowering drug (GLD) treatment in patients with T2D with high CV disease risk profile . As part of the CVD‐REAL study programme designed to study the effects of SGLT‐2 inhibitor treatment on CV outcomes in a real‐world setting, the CVD‐REAL Nordic Study, a large multinational observational study of >90 000 patients with T2D, has suggested the presence of SGLT‐2 inhibitor class effects by showing lower risk of CV mortality, major adverse CV events (MACE; non‐fatal myocardial infarction, non‐fatal stroke or CV mortality) and HHF compared with other GLDs; however, the comparator group used in that study, other GLDs, consisted of almost 50% patients with T2D treated with insulin or sulphonylureas, which have been shown to have increased associated CV risks compared with dipeptidyl peptidase‐4 (DPP‐4) inhibitors in previous observational studies . In addition, it is not fully clear to what extent this could have influenced the risk estimates.…”
Section: Introductionmentioning
confidence: 99%